Strategi Menurunkan Defisit Anggaran Tahun 2023 Dengan Pendekatan Analisis Proses Hierarki - Pratama, Mahir; Manurung, Lisman (Pusat Penelitian, Badan Keahlian DPR RI, 2024)
COVID-19 requires the Indonesian Government to implement financial policies for economic stability with the issuance of Law 2/2020 providing leeway for the government to project a budget deficit exceeding 3 percent of GDP from 2020-2022. This article wants to look at alternatives and government policy criteria to return the budget deficit to below 3 percent. The method uses the Analytic Hierarchy Process (AHP) with Expert Choice 11 software. Primary data is based on a purposive sampling method on 3 experts, namely APBN Analysts, Policy Economic Researchers and Financial Economic Observers as well as secondary data obtained from projections and realization of the 2020, 2021 and 2022 APBN. Central Statistics Agency and mainstream media with indicators, namely economic growth, exchange rate, inflation, oil prices and interest rates. The results of the AHP calculation sequentially from the high priority weights obtained the criteria for economic growth (0.325), interest rates (0.228), oil prices (0.203), inflation (0.139) and exchange rates (0.106). For alternatives, high priority weightings were obtained, namely tax revenue (0.238), trade balance (0.216), political stability (0.201), priority financing (0.179) and better spending (0.167). The role of the DPR RI is needed to supervise fiscal consolidation which is focused on three strategies, namely increasing revenue, better spending and financingAbstrakCOVID-19 mengharuskan Pemerintah Indonesia melakukan kebijakan keuangan untuk stabilitas ekonomi dengan terbitnya Undang-Undang No 2 Tahun 2020 memberikan kelonggaran kepada pemerintah untuk memproyeksikan defisit anggaran melebihi 3 persen dari PDB dari tahun 2020-2022. Tulisan ini ingin melihat alternatif dan kriteria kebijakan pemerintah untuk mengembalikan defisit anggaran di bawah 3 persen. Metode menggunakan Analytic Hierarchy Process (AHP) dengan software Expert Choice 11. Data primer berdasarkan metode purposive sampling pada 3 pakar yaitu Analis APBN, Peneliti Ekonomi Kebijakan dan Pengamat Ekonomi Keuangan serta data sekunder diperoleh dari proyeksi dan realisasi APBN tahun 2020, 2021 dan 2022, Badan Pusat Statistik dan media mainstream dengan indikator yaitu pertumbuhan ekonomi, nilai tukar, inflasi, harga minyak dan suku bunga. Hasil perhitungan AHP secara berurutan dari bobot prioritas tinggi diperoleh kriteria pertumbuhan ekonomi (0,325), suku bunga (0,228), harga minyak (0,203), inflasi (0,139) dan nilai tukar (0,106). Untuk alternatif diperoleh pembobotan prioritas tinggi yaitu penerimaan pajak (0,238), neraca perdagangan (0,216), stabilitas politik (0,201), pembiayaan prioritas (0,179) dan spending better (0,167). Diperlukan peran DPR RI untuk mengawasi konsolidasi fiskal yang difokuskan pada tiga strategi, yaitu peningkatan penerimaan, spending better, dan pembiayaan.